Neoliberal ethos, state censorship and sexual culture: a Chinese dating/hook-up app. Issue 5 (2nd September 2016) - Liu, Tingting
Abstract: Based upon the case of Momo, a popular Chinese dating/hook-up social media, this article examines an understudied aspect of social media: the kinds of sexual activities a social media tends to encourage, facilitate and mediate, and the sexual ideologies a social media site/application chooses to align with in its advertising and promotional strategies. With a critical conversation with existing scholarships concerning the intersections between feminist/queer theories and media studies, the article considers how sexualities can constitute a useful lens for understanding social media so as to provide a glimpse into the complex interconnections between political, cultural, economic and the 'private' realms of sexual experience.